1995
DOI: 10.1159/000246665
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing Fasciitis due to <i>Pasteurella multocida</i> Infection

Abstract: Necrotizing fasciitis is a potentially fatal clinical disease caused by infection with various bacteria in addition to streptococci, which are common causative agents. We report on a rare case of this disease in association with Pasteurella multocida infection. A 58-year-old man had systemic features of shock after a 15-hour history of a painful swelling on the right lower leg. The swelling led to skin blistering and necrosis from which P. multocida was isolated. Those lesions progressed rapidly. The patient a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
5

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 4 publications
0
13
0
5
Order By: Relevance
“…Vasculitic changes were noted in some vessels and considered a secondary rather than a primary phenomenon. Cocci were-identified in three of the specimens (Cases 6, 8,9) all of whom grew GABHS.…”
Section: Histopathologymentioning
confidence: 98%
“…Vasculitic changes were noted in some vessels and considered a secondary rather than a primary phenomenon. Cocci were-identified in three of the specimens (Cases 6, 8,9) all of whom grew GABHS.…”
Section: Histopathologymentioning
confidence: 98%
“…The method is based on an accurate measurement of the Gamow-Teller strength distribution, B(GT), as a function of excitation energy in the daughter nucleus, and relies on the technique of Total Absorption gamma Spectroscopy (TAgS) which will be explained later. The theoretical idea was suggested by Hamamoto et al [11] and pursued by Sarriguren et al [12]. According to them, one can study the deformation of the ground state of a particular nucleus by measuring the B(GT) distribution of its β-decay.…”
mentioning
confidence: 99%
“…Duration of therapy for these patients is less well defined. 1,8, 9 Currently, there is very limited information concerning the use of aztreonam in the treatment of P. multocida infections. An exhaustive literature review found only 3 in vitro studies testing aztreonam against P. multocida isolates, all of which were inhibited by aztreonam.…”
Section: Discussionmentioning
confidence: 99%